Phase-field-based calculations of the disregistry fields of static extended dislocations in FCC metals. Issue 11 (3rd June 2019) - Xu, Shuozhi; Mianroodi, Jaber R.; Hunter, Abigail; Beyerlein, Irene J.; Svendsen, Bob
ABSTRACT: In the continuum context, the displacements of atoms induced by a dislocation can be approximated by a continuum disregistry field. In this work, two phase-field (PF)-based approaches and their variants are employed to calculate the disregistry fields of static, extended dislocations of pure edge and pure screw character in two face-centred cubic metals: Au and Al, which have distinct stable stacking fault energy and elastic anisotropy. A new truncated Fourier series form is developed to approximate the generalised stacking fault energy (GSFE) surface, which shows significant improvement over the previously employed Fourier series form. By measuring the intrinsic stacking fault (ISF) width and partial dislocation core size in different ways, the PF-based disregistry fields are quantitatively compared against those predicted by molecular statics. In particular, two new measures for the ISF widths are proposed and shown to overcome drawbacks of the more commonly used standards in the literature. Our calculations also show that continuum formulation of the elastic energy and the GSFE for a homogeneous surface can successfully characterise the core structure. Last, our comparisons highlight the significance of including the gradient energy in the free energy formulation when an accurate description of the dislocation core structure is desired.